Foreword to WIS 2018: Special Issue on: “Fighting Inequalities” - Reima Suomi; Hongxiu Li; Ágústa Pálsdóttir; Roland Trill (Sosiaali- ja terveyshuollon tietojenkäsittely-yhdistys, 2022)
In August 2018 the seventh conference in the series “Well-being in the Information Society” (WIS 2018) was organized in Turku, in co-operation between University of Turku and the Baltic Region Healthy Cities Association. The conference focused on inequalities in our societies representing an active approach called “Fighting Inequalities”. Inequality describes in general an unfair situation in which some people have more rights or better opportunities than other people. Health(care) inequalities or those in welfare can be defined as differences in health status or in the distribution of health determinants between different population groups, for example, differences in mobility between elderly people and younger populations or differences in mortality rates between people from different social classes. A growing number of inequalities are related to different competences and skills in the exploding information society, for example different access to information and data. Some health inequalities are attributable to biological variations or free choice and others are attributable to the external environment and conditions mainly outside the control of the individuals concerned. In the first case it may be impossible or ethically or ideologically unacceptable to change the health determinants, and so the health inequalities are unavoidable. In the second, the uneven distribution may be unnecessary and avoidable as well as unjust and unfair, so that the resulting health inequalities also lead to inequity in health